The Philippine economy : no longer the East Asian exception? - Clarete, Ramon L.; Esguerra, Emmanuel F.; Hill, Hal, 1948- (Singapore : ISEAS-Yusof Ishak Institute, 2019)
In this volume, a leading group of scholars pose the question, has the Philippine economy rejoined the dynamic East Asian mainstream and, if so, what set of policies and priorities are required to maintain the strong economic momentum of recent years? Successive chapters address issues related to growth and poverty, infrastructure and urbanization, education, health, the environment, energy, development finance, and governance and institutions. This volume has been written with a broad audience in mind. First and foremost it is for readers in, and interested in, this fascinating and important country with a population that now exceeds 100 million people. Second, it will appeal to those in the broader development community with an interest in the analytical and policy challenges that democratic, middle-income countries face as they struggle to lift their citizens out of poverty and to achieve broad-based and environmentally sustainable growth.
Title from publisher's bibliographic system (viewed on 22 Feb 2019).
Keywords: Philippines -- Economic conditions